2018
DOI: 10.1071/ah16212
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of evidence underpinning non-pharmacological therapies in dementia

Abstract: Dementia is one of the most common illnesses worldwide, and is one of the most important causes of disability in older people. Currently, dementia affects over 35million people around the globe. It is expected that this number will increase to 65.7million by 2030. Early detection, diagnosis and treatment to control the principal behaviour symptoms may help reduce these numbers and delay the progression to more advanced and dangerous stages of this disorder with resultant increase quality of life for those affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…In people with Mild and Major NCD, for example, NPTs have been shown to be effective in improving apathy administered alone 11 or combined with drug therapy 14,15 . A summary of the NPTs employed to reduce apathy (as a direct or indirect target), and the clinical populations on which they have been employed is presented in Table 1 (see 11,14,16 for more exhaustive reviews).…”
Section: Introductionmentioning
confidence: 99%
“…In people with Mild and Major NCD, for example, NPTs have been shown to be effective in improving apathy administered alone 11 or combined with drug therapy 14,15 . A summary of the NPTs employed to reduce apathy (as a direct or indirect target), and the clinical populations on which they have been employed is presented in Table 1 (see 11,14,16 for more exhaustive reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal evidence has suggested that certain scents (e.g., lavender, lemon balm, cedar) may have mildly sedating properties when used in agitated people with dementia [172]. Few of these studies have examined sleep or specifically targeted nocturnal agitation as an outcome.…”
Section: Aromatherapymentioning
confidence: 99%
“…Music is one of the most studied activity interventions used to improve mood, such as agitation, and disruptive behavior for individuals with dementia (Olley & Morales, 2017). Overall, music interventions for individuals with dementia have involved either defined 'music therapy' programs (e.g., singing, music improvisation, playing instruments, and creating music) conducted by a credentialed music therapist or consisted of passive 'music listening' (e.g., pre-recorded or live music) not requiring a music therapist (Vink & Hanser, 2018).…”
Section: Music-based Interventionmentioning
confidence: 99%